Hubungan Kebiasaan Merokok dengan Kejadian Infark Miokard Akut (IMA) - Azra Nadhira Botutihe; Nasrun Pakaya; Erwin Purwanto (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between smoking habits and the incidence of Acute Myocardial Infarction (AMI) at Toto Kabila Regional Hospital, Bone Bolango Regency. The study used a cross-sectional method. The results showed a significant association between smoking habits and the incidence of Acute Myocardial Infarction (AMI) (p-value = 0.001). In conclusion, the heavier a person's smoking habit, the higher the likelihood of STEMI compared to NSTEMI.   Keywords: Risk Factors, Acute Myocardial Infarction (AMI), Smoking Habits, Heart Disease